2022
DOI: 10.3390/su14159103
|View full text |Cite
|
Sign up to set email alerts
|

Place Attachment, Cultural Involvement, and Residents’ Attitudes towards Tourism Development: The Case of Novi Sad, the European Capital of Culture 2022

Abstract: The purpose of this study was to determine how residents in Novi Sad (The European Capital of Culture 2022) perceive the influence of cultural involvement and place attachment on their attitude toward tourism, and how this affects their support for tourism development. In order to investigate the relationships between these factors, structural equation modeling (SEM) was used. The proposed model was tested, and the findings show significant relationships between residents’ cultural involvement, place attachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…More recent research on ECoC cities also emphasises the development of tourism in the context of resilient cities (Ivona et al, 2019), creating a path for more sustainable ECoC cultural tourism. The model for developing tourism in the ECoC context could also be monitored through cultural involvement, with place attachment, in terms of identity and dependence and a focus on positive and negative economic, socio-cultural, and environmental impacts (Blešić et al, 2022). The concept of transformative tourism within ECoC cities has been developed throughout the TraCEs project (Cultour is Capital, 2019), suggesting that there is a need for cooperation between ECoC cities, the CCI sector, and tourism stakeholders.…”
Section: Ecoc and (Cultural) Tourism Developmentmentioning
confidence: 99%
“…More recent research on ECoC cities also emphasises the development of tourism in the context of resilient cities (Ivona et al, 2019), creating a path for more sustainable ECoC cultural tourism. The model for developing tourism in the ECoC context could also be monitored through cultural involvement, with place attachment, in terms of identity and dependence and a focus on positive and negative economic, socio-cultural, and environmental impacts (Blešić et al, 2022). The concept of transformative tourism within ECoC cities has been developed throughout the TraCEs project (Cultour is Capital, 2019), suggesting that there is a need for cooperation between ECoC cities, the CCI sector, and tourism stakeholders.…”
Section: Ecoc and (Cultural) Tourism Developmentmentioning
confidence: 99%
“…Numerous research studies have made efforts to comprehend the process of how inhabitants of an area develop emotional connections to the places they live in within a tourist environment. Some of the studies which have been conducted in this area include research conducted by [12][13][14][15][16][17]. Despite the diversity in the areas of focus, some studies have also given attention to the context of heritage tourism, for instance, the research conducted by [18][19][20][21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Examples from this scale include "I would not substitute (this place) for any other area" and "this place is very special to me. " Since its development, it has been deployed in numerous studies and demonstrated to be previously reliable (see Blešić et al, 2022;Escolà-Gascón et al, 2023a;Escolà-Gascón et al, 2023b). A single outcome variable was computed for each participant by summing scale items, with a maximum score of 25 indicating greater place attachment.…”
Section: Measurement Of Place Attachment and Subjective Well-beingmentioning
confidence: 99%